Case Report: A 14-year-old boy with recurrent pancreatitis and autism—response to steroid and rituximab therapy - Lu, Yu-An; Lin, Chieh-Chung; Huang, Yen-Chu (Frontiers in Pediatrics, 2025)
We report the case of a 14-year-old boy with a history of recurrent pancreatitis, autism, and learning disabilities who presented with non-bilious vomiting, epigastric pain, and a progressively enlarging abdominal mass. He was diagnosed with IgG4-related autoimmune pancreatitis. Initial corticosteroid therapy achieved only temporary remission, with disease relapse occurring after 4 months. Rituximab was subsequently introduced, resulting in sustained disease control by depleting B lymphocytes and reducing disease flares, consistent with previous reports. The patient has remained clinically stable for 1 year. This case highlights the clinical presentation, diagnostic challenges, and therapeutic considerations of this rare condition.